Testing The Causal Relationship Between Imports And GDP In Syria - ديوب, محمد معن; حسن, علي (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research aims to study the relationship between imports and the gross domestic product in Syria, through the use of the Granger causality to determine the direction of the relationship in the short run, testing the co-integration and error correction model to detect the relationship in the long run, using the annual data obtained from the Central Bureau of Statistics during the period (2017 - 1975). The results of the co-integration test and the error correction model showed a bidirectional relationship between gross domestic product and imports, that is, there is a positive mutual effects between imports and gross domestic product in the long run. The result of Granger's test of causality in the short term showed that there is a unidirectional causal relationship that goes from imports to gross domestic product, meaning that changing imports leads to changing gross domestic product, but the opposite is not true. The results also showed an increase in the average tendency to import, and this indicates the importance of imports in the Syrian economy and the depth of its dependence on the forign market to obtain its needs, whether consumer or investment, and the fails of the import substitution policy, This was evidenced by the war period, when many products were scarce in the Syrian market, which was reflected in the increase in their prices.